Development of Novel Pharmaceutical Forms of the Marine Bioactive Pigment Echinochrome A Enabling Alternative Routes of Administration - Stefanos Kikionis; Paraskevi Papakyriakopoulou; Panagiotis Mavrogiorgis; Elena A. Vasileva; Natalia P. Mishchenko; Sergey A. Fedoreyev; Georgia Valsami; Efstathia Ioannou; Vassilios Roussis (Marine Drugs, 2023)
Echinochrome A (EchA), a marine bioactive pigment isolated from various sea urchin species, is the active agent of the clinically approved drug Histochrome®. EchA is currently only available in the form of an isotonic solution of its di- and tri-sodium salts due to its poor water solubility and sensitivity to oxidation. Electrospun polymeric nanofibers have lately emerged as promising drug carriers capable of improving the dissolution and bioavailability of drugs with limited water solubility. In the current study, EchA isolated from sea urchins of the genus Diadema collected at the island of Kastellorizo was incorporated in electrospun micro-/nanofibrous matrices composed of polycaprolactone and polyvinylpyrrolidone in various combinations. The physicochemical properties of the micro-/nanofibers were characterized using SEM, FT-IR, TGA and DSC analyses. The fabricated matrices exhibited variable dissolution/release profiles of EchA, as evidenced in in vitro experiments using gastrointestinal-like fluids (pH 1.2, 4.5 and 6.8). Ex vivo permeability studies using the EchA-loaded micro-/nanofibrous matrices showed an increased permeation of EchA across the duodenum barrier. The results of our study clearly show that electrospun polymeric micro-/nanofibers represent promising carriers for the development of new pharmaceutical formulations with controlled release, as well as increased stability and solubility of EchA, suitable for oral administration, while offering the potential for targeted delivery.